The role of customers and their privacy in an IoT business context - Cunha, Carlos R. (2021)
The Internet of Things has revolutionized the way we can think about sales and customer relationship management strategies. In this context, a view of the world where technology is embedded in practically all objects and physical spaces will be an expectable reality. This reality opens up unprecedented oppor- tunities with regard to the levels of customization in the sales process, whether in virtual spaces or in physical spaces. However, IoT also poses enormous chal- lenges in the field of security and in particular in the field of user privacy. In this context, this article, after analyzing some of the main challenges for IoT in the privacy domain and what impact the IoT may have in the business domain and in particular in the subdomains of sales and advertising, presents a conceptual model to support customer empowerment while citizen with regard to the definition and management of privacy policies concerns a context that may go beyond the bound- aries of citizenship and be applied in scenarios without borders, whenever there is the possibility of defining policies and legislation above Country.